Kudy k dinosaurům? O behaviorálním paradigmatu v podnikové informatice, paralelách k antropologii organizací a svazujících hranicích oborů - Michal Doležel (AntropoWebzin, 2013)
The main aim of this study is to introducethe behavioral research paradigm into theacademic discipline of Business Informatics (BI)in the Czech Republic. Its main motivation is thefact that design-oriented research traditionallydominates in this area and the word “informatics”is perceived mostly in its technical meaning(i.e. Computer Science) in Czech society. In mypaper I argue that there should be more sociallyoriented research in Czech BI and management,as well as less insistence upon quantitative researchmethods and/or design science. Fromthe perspective of a professionally qualified doctoralstudent, I firstly compare the Anglo-Saxonresearch tradition of Information Systems (IS)with the European one, as well as with the Czechtradition. Consequently I present underlyingmotivation and well-founded reasons for the behavioralresearch in BI, summarizing key topics.I also involved the researchers in social science inorder to form capable teams with researchers inbusiness and management. So far, there has alsobeen little discussion about the usage of anthropologicalconcepts and tools in BI and managementstudies. This study takes a transdisciplinary perspectiveand seeks to remedy all these challengesby reviewing of the literature in BI, IS, managementand organizational studies, socioculturalanthropology and business anthropology to reachthe conclusion that we need a more integrated approachin order to properly study such complexissues in modern business organizations andknowledge society.